2014
DOI: 10.1259/bjr.20130358
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neck shaft angle width is associated with hip-fracture risk in males but not independently of femoral neck bone density

Abstract: Objective: To investigate the specificity of the neck shaft angle (NSA) to predict hip fracture in males. Methods: We consecutively studied 228 males without fracture and 38 with hip fracture. A further 49 males with spine fracture were studied to evaluate the specificity of NSA for hip-fracture prediction. Femoral neck (FN) bone mineral density (FN-BMD), NSA, hip axis length and FN diameter (FND) were measured in each subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
2
24
0
4
Order By: Relevance
“…Most of the cross-sectional studies were also in postmenopausal Caucasian women but a few (26,28,30,31) included both men and women and 2 (32,33) were exclusively in men. All the studies including men found no association between HAL and hip fracture.…”
Section: Hip Axis Lengthmentioning
confidence: 99%
“…Most of the cross-sectional studies were also in postmenopausal Caucasian women but a few (26,28,30,31) included both men and women and 2 (32,33) were exclusively in men. All the studies including men found no association between HAL and hip fracture.…”
Section: Hip Axis Lengthmentioning
confidence: 99%
“…Проте сучасні можливості денситометрів не обмежу-ються визначенням показників МЩКТ, а й дають мож-ливість одночасного вивчення даних геометрії ПВ СК у поєднанні із показниками МЩКТ [12,[14][15][16][17]. Крім того, за допомогою ДРА є можливість долучати дані оцінки 10-річного ризику остеопоротичних перело-мів FRAX і показники якості кісткової тканини (TBS, Trabecular bone score) для оцінки ризику остеопоротич-них переломів.…”
Section: практична медицина / Practical Medicineunclassified
“…За даними C. Ripamonti, L. Lisi, M. Avella [23], у чоловіків без переломів -125,3 ± 4,9°, у хворих з пе-реломами СК цей показник становить 127,2 ± 6,2°, в осіб з клінічно значущими вертебральними перело-мами -126,4 ± 5,3°. Вимірювання даного показника є важливим не тільки для оцінки ризику ПСК, але й при підготовці хворого до оперативного втручання піс-ля остеопоротичного перелому.…”
unclassified
“…Проте сучасні можливості денситометрів не обмежуються визначенням показників МЩКТ, а й да-ють можливість одночасного вивчення даних геометрії ПВ СК у поєднанні із показниками МЩКТ [17,[21][22][23]28], а також долучати дані оцінки 10-річного ризику остеопоротичних переломів FRAX і показники якос-ті кісткової тканини (TBS, Trabecular bone score). Зо-браження шийки СК з вимірами довжини осі стегно-вої кістки та шийково-діафізарного кута за допомогою ДРА подано на рис.…”
unclassified
See 1 more Smart Citation